Language Resources and Evaluation - Ide, Nancy; Calzolari, Nicoletta; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer.)
Language Resources and Evaluation is the first publication devoted to the acquisition, creation, annotation, and use of language resources, together with methods for evaluation of resources, technologies, and applications. Language resources include language data and descriptions in machine readable form used to assist and augment language processing applications, such as written or spoken corpora and lexica, multimodal resources, grammars, terminology or domain specific databases and dictionaries, ontologies, multimedia databases, etc., as well as basic software tools for their acquisition, preparation, annotation, management, customization, and use. Evaluation of language resources concerns assessing the state-of-the-art for a given technology, comparing different approaches to a given problem, assessing the availability of resources and technologies for a given application, benchmarking, and assessing system usability and user satisfaction.
Keywords: Computer science; Linguistics; Computational linguistics; Philology; Computational Linguistics; Computer Science, general; Linguistics, general; Language and Literature